Complexation of Oligo- and Polynucleotides with Methoxyphenyl-Functionalized Imidazolium Surfactants - Darya A. Kuznetsova; Denis M. Kuznetsov; Leysan A. Vasileva; Syumbelya K. Amerhanova; Dilyara N. Valeeva; Diana V. Salakhieva; Viktoriia A. Nikolaeva; Irek R. Nizameev; Daut R. Islamov; Konstantin S. Usachev; Alexandra D. Voloshina; Lucia Ya. Zakharova (MDPI AG, 2022)
Interaction between cationic surfactants and nucleic acids attracts much attention due to the possibility of using such systems for gene delivery. Herein, the lipoplexes based on cationic surfactants with imidazolium head group bearing methoxyphenyl fragment (MPI-n, n = 10, 12, 14, 16) and nucleic acids (oligonucleotide and plasmid DNA) were explored. The complex formation was confirmed by dynamic/electrophoretic light scattering, transmission electron microscopy, fluorescence spectroscopy, circular dichroism, and gel electrophoresis. The nanosized lipoplex formation (of about 100-200 nm), contributed by electrostatic, hydrophobic interactions, and intercalation mechanism, has been shown. Significant effects of the hydrocarbon tail length of surfactant and the type of nucleic acid on their interaction was revealed. The cytotoxic effect and transfection ability of lipoplexes studied were determined using M-HeLa, A549 cancer cell lines, and normal Chang liver cells. A selective reduced cytotoxic effect of the complexes on M-HeLa cancer cells was established, as well as a high ability of the systems to be transfected into cancer cells. MPI-n/DNA complexes showed a pronounced transfection activity equal to the commercial preparation Lipofectamine 3000. Thus, it has been shown that MPI-n surfactants are effective agents for nucleic acid condensation and can be considered as potential non-viral vectors for gene delivery.